Validity of Thoracoscopic Esophagectomy and Lymph Node Dissection as a Radical Operation for Thoracic Esophageal Cancer Invading into the Adventitia - Taguchi, Shinichi; Kinoshita, Hiroaki; Takemura, Masashi; Fujiwara, Yuushi; Kaneko, Masahiro; Osugi, Harushi; Tanaka, Yoshinori; Fukuhara, Kenichiro; Nishizawa, Satoru; Lee, Shigeru (Nippon Shokaki Geka Gakkai zasshi, 2003)
Introduction: Validity of thoracoscopic esophagectomy and lymph node dissection as a radical operation for thoracic esophageal cancer invading the adventitia was retrospectively evaluated by comparing the results with that after esophagectomy through conventional thoracotomy.Materials and Methods: Subjects were 28 esophageal cancer patients with nodal involvement who underwent video-assisted thoracoscopic esophagectomy and lymphadenectomy after meeting indications of no extensive pleural adhesion, no contiguous tumor spread, and pulmonary function capable of sustaining single lung ventilation (VATS group). Controls were 39 esophageal cancer patients who met the same indications and underwent through right thoracotomy before VATS (control group).Results: No difference was seen in the background, duration of thoracic procedure or blood loss between groups. The 5-year survival rate was 53.6% in the VATS and 45.1% and in the control group, not statistically significant. Survival did not differ in the presence of lymph node metastasis between groups.Conclusions: The same radicality as open surgery can be obtained by VATS for patients with thoracic esophageal cancer invading the adventitia.